Limits of Blue and Green Infrastructures to Adapt Actual Urban Drainage Systems to the Impact of Climate Change - Benoit, Thomas; Martel, Jean-Luc; Bilodeau, Émilie; Brissette, François; Charron, Alain; Brulé, Dominic; Rivard, Gilles; Deslauriers, Simon (Journal of Irrigation and Drainage Engineering, 2025)
Keywords: Infolettre; Infolettre_Mars_2025

Disaster Risk Resilience: Conceptual Evolution, Key Issues, and Opportunities - Graveline, Marie-Hélène; Germain, Daniel (International Journal of Disaster Risk Science, 2022)
Abstract Resilience has become a cornerstone for risk management and disaster reduction. However, it has evolved extensively both etymologically and conceptually in time and across scientific disciplines. The concept has been (re)shaped by the evolution of research and practice efforts. Considered the opposite of vulnerability for a long time, resilience was first defined as the ability to resist, bounce back, cope with, and recover quickly from the impacts of hazards. To avoid the possible return to conditions of vulnerability and exposure to hazards, the notions of post-disaster development, transformation, and adaptation (build back better) and anticipation, innovation, and proactivity (bounce forward) were then integrated. Today, resilience is characterized by a multitude of components and several classifications. We present a selection of 25 components used to define resilience, and an interesting linkage emerges between these components and the dimensions of risk management (prevention, preparedness, response, and recovery), offering a perspective to strengthen resilience through the development of capacities. Despite its potential, resilience is subject to challenges regarding its operationalization, effectiveness, measurement, credibility, equity, and even its nature. Nevertheless, it offers applicability and opportunities for local communities as well as an interdisciplinary look at global challenges.

Urban flood resilience, a multi-level institutional analysis of planning practices in the Metropolitan City of Naples - Vitale, Corinne; Meijerink, Sander; Moccia, Francesco Domenico (Journal of Environmental Planning and Management, 2023)
Keywords: Ouvrage_Collectif_Numéro1

Disrupting the riskscapes of inequities: a case study of planning for resilience in Canada’s Metro Vancouver region - Yumagulova, Lilia (Cambridge Journal of Regions, Economy and Society, 2020)
Abstract The analysis across spatial, temporal and governance scales shows an inequitable distribution of risk across Canada’s Metro Vancouver region. For First Nation communities in this region, this risk is rooted in the colonial history of land dispossession. This article makes a contribution by expanding our understanding of historic creation of riskscapes and a discussion of its implications as a multiscale governance issue that persists across space and time. This article also situates the impacts of projected sea level rise on Indigenous communities in the context of regional, provincial and federal settler-colonial flood risk management regime.

Resilience patterns of human mobility in response to extreme urban floods - Tang, Junqing; Zhao, Pengjun; Gong, Zhaoya; Zhao, Hongbo; Huang, Fengjue; Li, Jiaying; Chen, Zhihe; Yu, Ling; Chen, Jun (National Science Review, 2023)
ABSTRACT Large-scale disasters can disproportionately impact different population groups, causing prominent disparity and inequality, especially for the vulnerable and marginalized. Here, we investigate the resilience of human mobility under the disturbance of the unprecedented ‘720’ Zhengzhou flood in China in 2021 using records of 1.32 billion mobile phone signaling generated by 4.35 million people. We find that although pluvial floods can trigger mobility reductions, the overall structural dynamics of mobility networks remain relatively stable. We also find that the low levels of mobility resilience in female, adolescent and older adult groups are mainly due to their insufficient capabilities to maintain business-as-usual travel frequency during the flood. Most importantly, we reveal three types of counter-intuitive, yet widely existing, resilience patterns of human mobility (namely, ‘reverse bathtub’, ‘ever-increasing’ and ‘ever-decreasing’ patterns), and demonstrate a universal mechanism of disaster-avoidance response by further corroborating that those abnormal resilience patterns are not associated with people’s gender or age. In view of the common association between travel behaviors and travelers’ socio-demographic characteristics, our findings provide a caveat for scholars when disclosing disparities in human travel behaviors during flood-induced emergencies.

Vulnerable Waters are Essential to Watershed Resilience - Lane, Charles R.; Creed, Irena F.; Golden, Heather E.; Leibowitz, Scott G.; Mushet, David M.; Rains, Mark C.; Wu, Qiusheng; D’Amico, Ellen; Alexander, Laurie C.; Ali, Genevieve A.; Basu, Nandita B.; Bennett, Micah G.; et al. (Ecosystems, 2023)
Abstract Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

Four core principles to reconcile sociocultural conditions and disaster risk reduction in pursuit of community resilience - Graveline, Marie-Hélène; Germain, Daniel; Boyer-Villemaire, Ursule; Guimond, Laurie (Environmental Hazards, 2025)
Keywords: Infolettre; Infolettre_Fevrier_2025

How Plans Prepare for Future Uncertainty: Integrating Land Change Modeling and the Plan Integration for Resilience Scorecard™ - Kim, Youjung; Newman, Galen; Berke, Philip; Lee, Jaekyung; Malecha, Matthew; Yu, Siyu (Journal of Planning Education and Research, 2024)
This study integrates Land Change Modeling with the Plan Integration for Resilience Scorecard™ methodology to assess coastal communities’ preparedness for uncertain future urban growth and flood hazards. Findings indicate that, under static climate conditions, the network of plans in Tampa is well prepared across all urban growth scenarios, but less so in the face of a changing climate. Specifically, scenario outputs that consider climate change suggest the need for more resilient growth to reduce flood vulnerability compared with the current land use plan. Notably, some existing policies are likely to lead to counterproductive outcomes in a future with more extensive flooding.
Keywords: Infolettre; Infolettre_Septembre_2024

Operating urban resilience strategies to face climate change and associated risks: some advances from theory to application in Canada and France - Heinzlef, Charlotte; Robert, Benoît; Hémond, Yannick; Serre, Damien (Cities, 2020)
Keywords: Hémond_Yannick; Ouvrage_Collectif_Numéro1

Urban resilience implementation: A policy challenge and research agenda for the 21st century - Coaffee, Jon; Therrien, Marie‐Christine; Chelleri, Lorenzo; Henstra, Daniel; Aldrich, Daniel P.; Mitchell, Carrie L.; Tsenkova, Sasha; Rigaud, Éric; the participants (Journal of Contingencies and Crisis Management, 2018)
Keywords: Ouvrage_Collectif_Numéro1

The “Lac-Mégantic tragedy” seen through the lens of the EnRiCH Community Resilience Framework for High-Risk Populations - Généreux, Mélissa; Petit, Geneviève; Roy, Mathieu; Maltais, Danielle; O’Sullivan, Tracey (Canadian Journal of Public Health, 2018)
Keywords: Généreux_Mélissa

A place-based model for understanding community resilience to natural disasters - Cutter, Susan L.; Barnes, Lindsey; Berry, Melissa; Burton, Christopher; Evans, Elijah; Tate, Eric; Webb, Jennifer (Global Environmental Change, 2008)

Retrofitting for Flood Resilience: A Guide to Building & Community Design - Barsley, Edward (RIBA Publishing, 2020)
Keywords: Ouvrage_Collectif_Numéro1

Energy poverty: an overlooked determinant of health and climate resilience in Canada - Riva, Mylène; Kingunza Makasi, Sophie; O’Sullivan, Kimberley C.; Das, Runa R.; Dufresne, Philippe; Kaiser, David; Breau, Sébastien (Canadian Journal of Public Health, 2023)
Abstract Objective Despite Canada being an important energy producer, not all Canadians can access or afford adequate levels of energy services at home to meet their needs, maintain healthy indoor temperatures, and live a decent life—a situation known as energy poverty. Depending on the measure, 6–19% of Canadian households face energy poverty. Health risks associated with energy poverty are documented in countries with milder climates. This study explores, for the first time in the Canadian context, the association between energy poverty and health. Methods Cross-sectional data are from the 2018 Canadian Housing Survey. Analyses are conducted on a sample weighted to represent 14 million Canadian households. The associations between expenditure-based and self-reported measures of energy poverty and self-rated general and mental health were assessed using logistic regression models, adjusted for potential confounding variables. Results The odds of rating one’s general (OR: 1.48; 95%CI: 1.29, 1.70) and mental (OR: 1.21; 1.04, 1.41) health as poor are significantly higher for Canadian adults in households with a high share of energy expenditure to income. The likelihood of poor general and mental health was significantly higher for those dissatisfied with the energy efficiency of their dwelling, and with their ability to maintain a comfortable temperature both in the winter and in the summer. Conclusion Exposure to energy poverty is associated with significantly increased likelihood of poor general and mental health. Given the high proportion of Canadian households facing energy poverty, with demonstrated implications for population health, tackling energy poverty is essential for an equitable energy transition and for climate resilience. , Résumé Objectif Bien que le Canada soit un important producteur d’énergie, entre 6 % et 19 % des ménages canadiens, selon la mesure retenue, sont en précarité énergétique, une situation qui survient lorsqu’un ménage n’a pas les moyens ou l’accès à des services énergétiques résidentiels adéquats pour maintenir une température ambiante confortable, répondre à ses besoins et vivre dans la dignité. Les risques socio-sanitaires associés à la précarité énergétique sont documentés dans des pays au climat tempéré. Cette étude explore, pour la première fois dans le contexte canadien, l’association entre la précarité énergétique et la santé. Méthodes Les données transversales proviennent de l’Enquête canadienne sur le logement de 2018. Les associations entre différentes mesures de précarité énergétique (mesures basées sur les dépenses des ménages et auto-rapportées) et la santé générale et mentale perçue sont estimées à l’aide de modèles de régression logistique ajustés pour des variables de confusion potentielles. Les analyses sont réalisées sur un échantillon pondéré pour représenter 14 millions de ménages. Résultats Les probabilités de déclarer une mauvaise santé générale (OR : 1,48; IC95% : 1,29-1,70) et mentale (OR : 1,21; 1,04-1,41) sont significativement plus élevées pour les adultes canadiens dont le ménage consacre une part importante de son revenu aux coûts énergétiques. Elles sont aussi significativement plus élevées pour ceux qui déclarent être insatisfaits avec l’efficacité énergétique de leur logement et de leur capacité à maintenir une température confortable en hiver et en été. Conclusion Vivre en situation de précarité énergétique est associée à des probabilités accrues de déclarer une mauvaise santé générale et mentale chez les adultes canadiens. En raison de la proportion élevée de ménages canadiens confrontés à la précarité énergétique et des effets socio-sanitaires que cette situation engendre, lutter contre la précarité énergétique est essentiel pour une transition énergétique équitable et pour la résilience climatique.

The Social Life of Heatwave in London: Recasting the Role of Community and Resilience - Nobert, Sebastien; Pelling, Mark (Framing Community Disaster Resilience, 2018)
Keywords: Nobert_Sebastien

From Policy Challenge to Implementation Strategy: Enabling Strategies for Network Governance of Urban Resilience - Therrien, Marie‐Christine; Normandin, Julie‐Maude (Risk, Hazards & Crisis in Public Policy, 2020)
What transformations do municipal administrations implement to enact a resilience policy? This article responds to this question from a comparative perspective by analyzing enabling and impeding mechanisms developed in the cities of Montreal (Canada) and London (UK) as they establish their strategies. Collaborative network governance and institutional work mechanisms used in Montreal and London are analyzed in connection with the influence of macro‐ and micro‐contextual elements under which a network can resiliently manage risk and crises. In both cases, the development of resilience emerges from their emergency management structures, as units in charge try to animate their new area of responsibility through collaborative governance. As a siloed approach this is embedded in daily routines, organizations with limited resources focused on shared motivation and values, collaboration across organizational boundaries and creation of joint capacity to implement resilience. This transformative process concerns the organization in charge of resilience in the municipal administration and the wider network that they build and animate. , 从政策挑战到落实战略: 为都市韧性网络管理创造战略 自治政府为颁布一项韧性政策会经历哪些转型?本文透过比较视角, 通过分析蒙特利尔(加拿大)和伦敦(英国)在建立各自战略时开发的推动机制和阻碍机制, 对该疑问进行了回应。分析了蒙特利尔和伦敦所使用的协作网络治理及机构工作机制与“宏观和微观情境元素的影响”之间的关系, 在这些情境元素中网络能发挥韧性管理风险和危机。在这两个案例中, 当应急管理结构中各主管单位试图通过协作治理开启新的责任区时, 韧性便得以发展。作为一项孤立的措施, 其被应用于日常活动中、应用于在共享动机和价值观方面资源有限的机构中、还被用于跨组织界限的协作以及为发挥韧性而创造的共同行动。该转型过程与负责自治政府韧性建设的机构有关, 还与后者建立和推动的更广网络有关。 , Del desafío político a la estrategia de implementación: estrategias habilitantes para la gobernanza de la red de resiliencia urbana ¿Qué transformaciones implementan las administraciones municipales para promulgar una política de resiliencia? Este artículo responde a esta pregunta desde una perspectiva comparativa analizando los mecanismos habilitadores e impedidores desarrollados en las ciudades de Montreal (Canadá) y Londres (Reino Unido) a medida que establecen sus estrategias. La gobernanza de la red colaborativa y los mecanismos de trabajo institucional utilizados en Montreal y Londres se analizan en relación con la influencia de elementos macro y micro contextuales bajo los cuales una red puede gestionar de manera resiliente los riesgos y las crisis. En ambos casos, el desarrollo de la resiliencia surge de sus estructuras de gestión de emergencias, ya que las unidades a cargo intentan animar su nueva área de responsabilidad a través de la gobernanza colaborativa. Como un enfoque aislado, esto se integra en las rutinas diarias, las organizaciones con recursos limitados se centraron en la motivación y los valores compartidos, la colaboración a través de los límites de la organización y la creación de capacidad conjunta para implementar la resiliencia. Este proceso transformador concierne a la organización a cargo de la resiliencia en la administración municipal y la red más amplia que construyen y animan.

A review of the flood risk management governance and resilience literature - Morrison, A.; Westbrook, C.J.; Noble, B.F. (Journal of Flood Risk Management, 2018)
The environmental management literature suggests that resilience is key to managing complex systems and reducing vulnerability resulting from uncertainty and unexpected change. Yet, flood risk management (FRM) has emerged largely from a culture of resistance. This paper takes the pulse of the current state of FRM research, with a focus on how the scholarly community has approached governance for flood resilience. Our analysis of the FRM journal literature identified 258 articles addressing governance and flooding, resilience and adaptation. Five main research themes emerged from these articles, addressing a variety of issues, but mostly lacking the degree of integration needed to address the social‐ecological complexity of FRM. Overall, research supporting the governance of FRM for resilience lacks integration, and methods of mitigating this lack of integration are poorly studied. We conclude with a discussion about the nature and scope of FRM research for resilience, and identify opportunities for more integrative FRM research that is more tightly coupled with policy and practice.
Keywords: Ouvrage_Collectif_Numéro1

Improving flood resilience through governance strategies: Gauging the state of the art - Matczak, Piotr; Hegger, Dries (WIREs Water, 2021)
Abstract There has been an upsurge in studies of flood risk governance (FRG): steering and decision‐making by public and private actors as a complement to risk assessments and technical management options. The scholarly debate is, however, highly fragmented, complicating the production of cumulative insights. To address this knowledge gap, we used six governance strategies for achieving flood resilience that previously have been put forward as a conceptual framework to review 121 articles published between 2016 and 2019, complemented with insights contained in recent overview articles, to gauge the state‐of‐the‐art in FRG literature: to (a) diversify flood risk management strategies; (b) align the strategies; (c) adequately involve private actors, including citizens; (d) put an adequate rule system in place; (e) cater for sufficient monetary and non‐monetary resources; (f) inspire an open and inclusive normative debate. We found, first, that literature is producing insights on increasingly technically advanced risk assessments and agent‐based models but societal debate on justice in flood risk governance is getting attention. A clearly emerging topic is that of citizen engagement in flood risk governance. Second, the geographical focus of the studies is still skewed toward the Global North. To make progress in understanding flood risk governance for better resilience more systematic and comparative empirical assessments of flood risk governance in order to derive generalizable lessons while better taking into account the context‐specificity of FRG. Testing flood risk governance solutions against comparative cases, by balancing the geographical scope of research efforts, and enhancing interdisciplinary and transdisciplinary working is a way to deliver knowledge for more resilience. This article is categorized under: Human Water > Water Governance Engineering Water > Planning Water
Keywords: Ouvrage_Collectif_Numéro1

Changes in mortality and economic vulnerability to climatic hazards under economic development at the provincial level in China - Wu, Jidong; Li, Ying; Ye, Tao; Li, Ning (Regional Environmental Change, 2019)

Limited progress in global reduction of vulnerability to flood impacts over the past two decades - Sauer, Inga J.; Mester, Benedikt; Frieler, Katja; Zimmermann, Sandra; Schewe, Jacob; Otto, Christian (Communications Earth & Environment, 2024)
Abstract Global flood impacts have risen in recent decades. While increasing exposure was the dominant driver of surging impacts, counteracting vulnerability reductions have been detected, but were too weak to reverse this trend. To assess the ongoing progress on vulnerability reduction, we combine a recently available dataset of flooded areas derived from satellite imagery for 913 events with four global disaster databases and socio-economic data. Event-specific flood vulnerabilities for assets, fatalities and displacements reveal a lack of progress in reducing global flood vulnerability from 2000—2018. We examine the relationship between vulnerabilities and human development, inequality, flood exposure and local structural characteristics. We find that vulnerability levels are significantly lower in areas with good structural characteristics and significantly higher in low developed areas. However, socio-economic development was insufficient to reduce vulnerabilities over the study period. Nevertheless, the strong correlation between vulnerability and structural characteristics suggests further potential for adaptation through vulnerability reduction.

Methodological approach for mapping the flood physical vulnerability index with geographical open-source data: an example in a small-middle city (Ponferrada, Spain) - Tascón-González, Laura; Ferrer-Julià, Montserrat; García-Meléndez, Eduardo (Natural Hazards, 2024)
Abstract To increase the resilience of communities against floods, it is necessary to develop methodologies to estimate the vulnerability. The concept of vulnerability is multidimensional, but most flood vulnerability studies have focused only on the social approach. Nevertheless, in recent years, following seismic analysis, the physical point of view has increased its relevance. Therefore, the present study proposes a methodology to map the flood physical vulnerability and applies it using an index at urban parcel scale for a medium-sized town (Ponferrada, Spain). This index is based on multiple indicators fed by geographical open-source data, once they have been normalized and combined with different weights extracted from an Analytic Hierarchic Process. The results show a raster map of the physical vulnerability index that facilitates future emergency and flood risk management to diminish potential damages. A total of 22.7% of the urban parcels in the studied town present an index value higher than 0.4, which is considered highly vulnerable. The location of these urban parcels would have passed unnoticed without the use of open governmental datasets, when an average value would have been calculated for the overall municipality. Moreover, the building percentage covered by water was the most influential indicator in the study area, where the simulated flood was generated by an alleged dam break. The study exceeds the spatial constraints of collecting this type of data by direct interviews with inhabitants and allows for working with larger areas, identifying the physical buildings and infrastructure differences among the urban parcels.

Psychosocial vulnerability and demographic characteristics in extreme flash floods: The case of Mandra 2017 flood in Greece - Speis, Phoebe-Demeter; Andreadakis, Emmanuel; Diakakis, Michalis; Daidassi, Evanthia; Sarigiannis, Georgios (International Journal of Disaster Risk Reduction, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Weaponizing vulnerability to climate change - Thomas, Kimberley Anh; Warner, Benjamin P. (Global Environmental Change, 2019)

Qualitative Assessment of Social Vulnerability to Flood Hazards in Romania - Török, Ibolya (Sustainability, 2018)
This paper investigates local-scale social vulnerability to flood hazards in Romania, aiming to identify the most vulnerable social and demographic groups across a wide range of geographical locations by considering three dimensions: demographic, socioeconomic, and the built environment. The purpose of the paper is threefold: first, it strives to improve the Social Vulnerability model (SoVI®) by applying a different weighting method adapted to the Romanian context, taking into consideration the municipalities exposed to flood movements. Second, it aims to develop an assessment model for the most vulnerable communities by measuring the heterogeneity according to local indicators related to disaster risks. Third, it aims to facilitate emergency managers to identify community sub-groups that are more susceptible to loss and to increase the resilience of local communities. To perform local-level vulnerability mapping, 28 variables were selected and three aggregated indexes were constructed with the help of the ArcGIS software. Moreover, a model of Geographically Weighted Regression (GWR) between communities directly affected by floods and localities with high- and very high values of the Local Social Vulnerability Index (LoSoVI) was used to explore the spatial relationship among them and to compare the appropriateness of Ordinary Least Square (OLS) and GWR for such modelling. The established GWR model has revealed that the negative effects of flood hazards are often associated with communities with a high degree of social vulnerability. Thus, the analysis is able to provide a more comprehensive picture on communities in desperate need of financial resources in order to have the ability to diminish the negative impacts of flood hazards and to provide a more sustainable society.

Analyser la vulnérabilité sociétale et territoriale aux inondations en milieu urbain dans le contexte des changements climatiques, en prenant comme cas d'étude la Ville de Montréal - Thomas, I.; Bleau, N. (2018)
28 Figure 7 : limites de la zone inondable et la zone inondée historiquement de la rive de Montréal de la rivière des prairies. [...] 68 Figure 27 : Aperçu de la table d’attributs de la base des données de la description de la sensibilité territoriale. [...] 41 Graphique 3 : Distribution des degrés de la sensibilité sociale par nombre d’aires de diffusion (206 AD au total) du secteur de la rivière des Prairies à Montréal à partir des résultats de l’indice ISSAIP des groupes de l’atelier de travail. [...] Cette analyse implique plusieurs étapes et le développement de plusieurs outils dont : la collecte des données disponibles et nécessaires pour réaliser un état des lieux des zones inondées historiquement pour une partie de la Ville de Montréal, la modélisation de l'espace occupé par l'eau selon différents niveaux d'eau possiblement atteints lors de débordement de la rivière, la collecte des donnée. [...] : la formation de réseaux de communication, la prise de décision, la création de consensus), qu’il est possible de mesurer, mais pas au moyen de données d’archives secondaires.
Keywords: Thomas_Isabelle

Adaptation policy and community discourse: risk, vulnerability, and just transformation - Schlosberg, David; Collins, Lisette B.; Niemeyer, Simon (Environmental Politics, 2017)

An Empirical Social Vulnerability Map for Flood Risk Assessment at Global Scale (“GlobE‐SoVI”) - Reimann, Lena; Koks, Elco; De Moel, Hans; Ton, Marijn J.; Aerts, Jeroen C. J. H. (Earth's Future, 2024)
Abstract Fatalities caused by natural hazards are driven not only by population exposure, but also by their vulnerability to these events, determined by intersecting characteristics such as education, age and income. Empirical evidence of the drivers of social vulnerability, however, is limited due to a lack of relevant data, in particular on a global scale. Consequently, existing global‐scale risk assessments rarely account for social vulnerability. To address this gap, we estimate regression models that predict fatalities caused by past flooding events ( n = 913) based on potential social vulnerability drivers. Analyzing 47 variables calculated from publicly available spatial data sets, we establish five statistically significant vulnerability variables: mean years of schooling; share of elderly; gender income gap; rural settlements; and walking time to nearest healthcare facility. We use the regression coefficients as weights to calculate the “ Glob al‐ E mpirical So cial V ulnerability I ndex (GlobE‐SoVI)” at a spatial resolution of ∼1 km. We find distinct spatial patterns of vulnerability within and across countries, with low GlobE‐SoVI scores (i.e., 1–2) in for example, Northern America, northern Europe, and Australia; and high scores (i.e., 9–10) in for example, northern Africa, the Middle East, and southern Asia. Globally, education has the highest relative contribution to vulnerability (roughly 58%), acting as a driver that reduces vulnerability; all other drivers increase vulnerability, with the gender income gap contributing ∼24% and the elderly another 11%. Due to its empirical foundation, the GlobE‐SoVI advances our understanding of social vulnerability drivers at global scale and can be used for global (flood) risk assessments. , Plain Language Summary Social vulnerability is rarely accounted for in global‐scale risk assessments. We develop an empirical social vulnerability map (“GlobE‐SoVI”) based on five key drivers of social vulnerability to flooding, that is, education, elderly, income inequality, rural settlements and travel time to healthcare, which we establish based on flood fatalities caused by past flooding events. Globally, we find education to have a high and reducing effect on social vulnerability, while all other drivers increase vulnerability. Integrating social vulnerability in global‐scale (flood) risk assessments can help inform global policy frameworks that aim to reduce risks posed by natural hazards and climate change as well as to foster more equitable development globally. , Key Points We develop a global map of social vulnerability at ∼1 km spatial resolution based on five key vulnerability drivers (“GlobE‐SoVI”) We establish vulnerability drivers empirically based on their contribution to predicting fatalities caused by past flooding events Accounting for social vulnerability in global‐scale (flood) risk assessments can inform global policy frameworks that aim to reduce risk

Looking for capacities rather than vulnerabilities: The moderating effect of health assets on the associations between adverse social position and health - Roy, Mathieu; Levasseur, Mélanie; Doré, Isabelle; St-Hilaire, France; Michallet, Bernard; Couturier, Yves; Maltais, Danielle; Lindström, Bengt; Généreux, Mélissa (Preventive Medicine, 2018)
Keywords: Généreux_Mélissa

Assessing the vulnerability of urban drinking water intakes to water scarcity under global change: A bottom-up approach - Leveque, Baptiste; Irakiza Shyaka, Albert; Ndong, Mouhamed; Jalbert, Jonathan; Burnet, Jean-Baptiste; Kammoun, Raja; Dorner, Sarah; Bichai, Françoise (Environmental Challenges, 2024)
Keywords: Dorner_Sarah

Comparing spatially explicit approaches to assess social vulnerability dynamics to flooding - Meijer, L.G.; Reimann, L.; Aerts, J.C.J.H. (International Journal of Disaster Risk Reduction, 2023)

Impact of climate change on the vulnerability of drinking water intakes in a northern region - Leveque, B.; Burnet, J.-B.; Dorner, S.; Bichai, F. (Sustainable Cities and Society, 2021)
Keywords: Dorner_Sarah

Spatial Analysis of Social Vulnerability to Floods Based on the MOVE Framework and Information Entropy Method: Case Study of Katsushika Ward, Tokyo - Lianxiao; Morimoto, Takehiro (Sustainability, 2019)
Tokyo is located in a lowland area that is vulnerable to flooding. Due to global climate change, the scalability and frequency of flooding is increasing. On the other hand, population aging and family structural changes, as well as the lack of adaptation measures, would accelerate flooding vulnerability. The key factors involved in social vulnerability must be studied to reduce the risk of flooding. In this study, we refer to the MOVE framework (a disaster vulnerability assessment framework) and analyze it from three perspectives: Exposure to social vulnerability, susceptibility, and resilience. We subsequently develop an index system to complete the evaluation using 11 indicators. The collected data will help reveal social vulnerability to floods in the Katsushika Ward, Tokyo, using the information entropy method and GIS. We found that the western region of the Katsushika Ward is at more risk than the eastern region during flooding. Additionally, the possibility of a serious crisis erupting is greater in the southwestern region than in the northwestern region. Consequently, we conclude that the spatial distribution of flooding varies in the region. The results of this study will help in understanding social vulnerability, in selecting and combining adaptation measures suited to the characteristics of the area, and in the effective and efficient implementation of these measures by the local government’s disaster department.

Development of a damage simulator for probabilistic seismic vulnerability assessment of electrical installations - Hosseinpour, Vahid; Saeidi, Ali; Nastev, Miroslav; Nollet, Marie-José (International Journal of Disaster Risk Reduction, 2025)

Integrating social vulnerability into high-resolution global flood risk mapping - Fox, Sean; Agyemang, Felix; Hawker, Laurence; Neal, Jeffrey (Nature Communications, 2024)
Abstract High-resolution global flood risk maps are increasingly used to inform disaster risk planning and response, particularly in lower income countries with limited data or capacity. However, current approaches do not adequately account for spatial variation in social vulnerability, which is a key determinant of variation in outcomes for exposed populations. Here we integrate annual average exceedance probability estimates from a high-resolution fluvial flood model with gridded population and poverty data to create a global vulnerability-adjusted risk index for flooding (VARI Flood) at 90-meter resolution. The index provides estimates of relative risk within or between countries and changes how we understand the geography of risk by identifying ‘hotspots’ characterised by high population density and high levels of social vulnerability. This approach, which emphasises risks to human well-being, could be used as a complement to traditional population or asset-centred approaches.

On mapping urban community resilience: Land use vulnerability, coping and adaptive strategies in Ghana - Ibrahim, Abdul-Salam; Kuuire, Vincent; Kepe, Thembela (Journal of Environmental Management, 2024)

Declining vulnerability but rising impacts: the trends of climatic disasters in Nepal - Chapagain, Dipesh; Bharati, Luna; Borgemeister, Christian (Regional Environmental Change, 2022)
Abstract The impacts of climatic disasters have been rising globally. Several studies argue that this upward trend is due to rapid growth in the population and wealth exposed to disasters. Others argue that rising extreme weather events due to anthropogenic climate change are responsible for the increase. Hence, the causes of the increase in disaster impacts remain elusive. Disaster impacts relative to income are higher in low-income countries, but existing studies are mostly from developed countries or at the cross-country level. Here we assess the spatiotemporal trends of climatic disaster impacts and vulnerability and their attribution to climatic and socioeconomic factors at the subnational scale in a low-income country, using Nepal as a case study. Loss of life is the most extreme consequence of disasters. Therefore, we employed human mortality as a measure of disaster impacts, and mortality normalized by exposed population as a measure of human vulnerability. We found that climatic disaster frequency and mortality increased in Nepal from 1992 to 2021. However, vulnerability decreased, most likely due to economic growth and progress in disaster risk reduction and climate change adaptation. Disaster mortality is positively correlated with disaster frequency and negatively correlated with per capita income but is not correlated with the exposed population. Hence, population growth may not have caused the rise in disaster mortality in Nepal. The strong rise in disaster incidence, potentially due to climate change, has overcome the effect of decreasing vulnerability and caused the rise in disaster mortality.

Leveraging Hazard, Exposure, and Social Vulnerability Data to Assess Flood Risk to Indigenous Communities in Canada - Chakraborty, Liton; Thistlethwaite, Jason; Minano, Andrea; Henstra, Daniel; Scott, Daniel (International Journal of Disaster Risk Science, 2021)
Abstract This study integrates novel data on 100-year flood hazard extents, exposure of residential properties, and place-based social vulnerability to comprehensively assess and compare flood risk between Indigenous communities living on 985 reserve lands and other Canadian communities across 3701 census subdivisions. National-scale exposure of residential properties to fluvial, pluvial, and coastal flooding was estimated at the 100-year return period. A social vulnerability index (SVI) was developed and included 49 variables from the national census that represent demographic, social, economic, cultural, and infrastructure/community indicators of vulnerability. Geographic information system-based bivariate choropleth mapping of the composite SVI scores and of flood exposure of residential properties and population was completed to assess the spatial variation of flood risk. We found that about 81% of the 985 Indigenous land reserves had some flood exposure that impacted either population or residential properties. Our analysis indicates that residential property-level flood exposure is similar between non-Indigenous and Indigenous communities, but socioeconomic vulnerability is higher on reserve lands, which confirms that the overall risk of Indigenous communities is higher. Findings suggest the need for more local verification of flood risk in Indigenous communities to address uncertainty in national scale analysis.

Environmental vulnerability and resilience: Social differentiation in short‐ and long‐term flood impacts - Houston, Donald; Werritty, Alan; Ball, Tom; Black, Andrew (Transactions of the Institute of British Geographers, 2021)
This paper finds that social differentiation in flood impacts is relatively small soon after a flood, with some surprising results such as professionals and homeowners badly affected in the short‐term – but widens over time, with socially disadvantaged groups displaying less recovery. The paper concludes that vulnerability and resilience to flooding are sensitive to financial resources, institutional support (chiefly from a landlord), and capacity to deal with disruption (chiefly time availability, which is low among professionals and high among retired people). An implication of these findings is that existing indices of flood vulnerability that use multiple measures of social deprivation should be used with caution, as not all conventional aspects of social deprivation are necessarily associated with greater vulnerability to flood impacts. , This paper reports household questionnaire survey results on vulnerability and resilience to flooding from one of the largest and most representative samples ( n = 593) of households up to 12 years after they were flooded, and is one of the first to provide detailed analysis of social differentiation in long‐term flood impacts. A novel finding is that social differentiation in flood impacts is relatively small soon after a flood, but widens over time, with socially disadvantaged groups displaying less recovery. The patterns of social differentiation in vulnerability and resilience to flooding differ markedly according to the type and timescale of the impact, with some normally socially advantaged groups (e.g., professionals and homeowners) being most vulnerable to short‐term impacts. Consistent with some existing studies, we found that older residents (age 70+) have greater resilience to flood impacts, although our sample may not capture the frailest individuals. As in previous research, low income is linked to lower resilience, particularly in the long term. We find that prior experience of flooding, despite enhancing preparedness, overall erodes rather than enhances resilience to flooding. Flood warnings are effective at reducing vulnerability to short‐term impacts. Underlying influences on resilience to natural disasters are complex and may only be revealed by multivariate analysis and not always be evident in simple observed patterns. The paper concludes that vulnerability and resilience to flooding are sensitive to financial resources, institutional support (chiefly from a landlord), and capacity to deal with disruption (chiefly time availability, which is low among professionals and high among retired people). An implication of these findings is that existing indices of flood vulnerability that use multiple measures of social deprivation should be used with caution, as not all conventional aspects of social deprivation are necessarily associated with greater vulnerability to flood impacts.

Empirical evidence of declining global vulnerability to climate-related hazards - Formetta, Giuseppe; Feyen, Luc (Global Environmental Change, 2019)

Application of Social Vulnerability Index (SoVI) and delineation of natural risk zones in Greater Lisbon, Portugal - Guillard-Gonçalves, Clémence; Cutter, Susan L.; Emrich, Christopher T.; Zêzere, José Luís (Journal of Risk Research, 2015)

Integrating social vulnerability into federal flood risk management planning - Cutter, S.L.; Emrich, C.T.; Morath, D.P.; Dunning, C.M. (Journal of Flood Risk Management, 2013)
Abstract While flood risk management planning in the U nited S tates has focused on flood control structures designed to protect the economic value of property, it has consistently undervalued other social impacts associated with flooding. The US A rmy C orps of E ngineers ( USACE ) recently initiated research aimed at understanding how to incorporate social characteristics into the measures currently utilised in flood control project evaluation and consideration. This paper proposes a methodology for incorporating a known measure of social vulnerability, the S ocial V ulnerability I ndex ( SoVI ), into USACE civil works planning. Using the USACE S outh A tlantic D ivision as the study area, this paper evaluates eight different variations of the social vulnerability metric and their potential deployment in USACE projects. Each formulation is compared with the original‐computed SoVI as a means to test its spatial and statistical sensitivity, including an assessment of each variant's robustness, reducibility, scalability, and transferability. Results indicate that while it is possible to create simplified, yet robust, versions of SoVI for individual places, such ‘lite’ metrics tend to fall short in areas of scalability and transferability in relation to the original SoVI formulation.

Improving GALDIT-based groundwater vulnerability predictive mapping using coupled resampling algorithms and machine learning models - Barzegar, Rahim; Razzagh, Siamak; Quilty, John; Adamowski, Jan; Kheyrollah Pour, Homa; Booij, Martijn J. (Journal of Hydrology, 2021)

Modification of the DRASTIC Framework for Mapping Groundwater Vulnerability Zones - Barzegar, Rahim; Asghari Moghaddam, Asghar; Norallahi, Shahrokh; Inam, Azhar; Adamowski, Jan; Alizadeh, Mohammad Reza; Bou Nassar, Jessica (Groundwater, 2020)
Abstract The DRASTIC technique is commonly used to assess groundwater vulnerability. The main disadvantage of the DRASTIC method is the difficulty associated with identifying appropriate ratings and weight assignments for each parameter. To mitigate this issue, ratings and weights can be approximated using different methods appropriate to the conditions of the study area. In this study, different linear (i.e., Wilcoxon test and statistical approaches) and nonlinear (Genetic algorithm [GA]) modifications for calibration of the DRASTIC framework using nitrate (NO 3 ) concentrations were compared through the preparation of groundwater vulnerability maps of the Meshqin‐Shahr plain, Iran. Twenty‐two groundwater samples were collected from wells in the study area, and their respective NO 3 concentrations were used to modify the ratings and weights of the DRASTIC parameters. The areas found to have the highest vulnerability were in the eastern, central, and western regions of the plain. Results showed that the modified DRASTIC frameworks performed well, compared to the unmodified DRASTIC. When measured NO 3 concentrations were correlated with the vulnerability indices produced by each method, the unmodified DRASTIC method performed most poorly, and the Wilcoxon–GA–DRASTIC method proved optimal. Compared to the unmodified DRASTIC method with an R 2 of 0.22, the Wilcoxon–GA–DRASTIC obtained a maximum R 2 value of 0.78. Modification of DRASTIC parameter ratings was found to be more efficient than the modification of the weights in establishing an accurately calibrated DRASTIC framework. However, modification of parameter ratings and weights together increased the R 2 value to the highest degree. , Article impact statement : The results showed that both linear and nonlinear methods are useful in modifying the ratings and weights of the DRASTIC method for assessing the groundwater vulnerability.

A place-based socioeconomic status index: Measuring social vulnerability to flood hazards in the context of environmental justice - Chakraborty, Liton; Rus, Horatiu; Henstra, Daniel; Thistlethwaite, Jason; Scott, Daniel (International Journal of Disaster Risk Reduction, 2020)
Keywords: Ouvrage_Collectif_Numéro1

Determinants of Risk: Exposure and Vulnerability - Cardona, Omar-Dario; Van Aalst, Maarten K.; Birkmann, Jörn; Fordham, Maureen; McGregor, Glenn; Perez, Rosa; Pulwarty, Roger S.; Schipper, E. Lisa F.; Sinh, Bach Tan; Décamps, Henri; Keim, Mark; Davis, Ian; et al. (Managing the Risks of Extreme Events and Disasters to Advance Climate Change Adaptation, 2012)
Keywords: Ouvrage_Collectif_Numéro1